Leitmotiv in perspectives on didactics of languages and cultures - Messak, Malika; FAID, Salah (Journal of Social Sciences and Humanities, 2025)
Reflection on language often provokes a parallel reflection on culture, and vice versa. In the global context, the French language is not only a tool of communication but also a vector of memory and culture. Any questioning of its role and influence raises the question of its cultural dimension and its links with teaching, where teachers aspire to promote a cultural openness. From a cultural perspective, this article examines language and culture teaching (DLC) as a discipline of intervention. Its objective is to establish and strengthen the link between the French language taught and its culture, considered as a perfect match forming a homogeneous and meaningful whole. To this end, we analyze the theoretical foundations of culture in the didactics of French as a foreign language (D.FFL) and examine the main areas of reflection. Our descriptive analysis addresses the following topics in succession: the position and complexity of DLC, the semantic field of culture and its fundamental concepts, concrete didactic proposals, and the place of culture in language teaching methodologies. Finally, the article highlights the new roles assigned to teachers and learners in this context.